Implementasi Pasal 4 ayat (1) Undang-Undang Nomor 21 Tahun 2000 tentang Serikat Pekerja/Serikat Buruh Oleh Dewan Pimpinan Daerah Konfederasi Serikat Pekerja Seluruh Indonesia Daerah Istimewa Yogyakarta (Studi Kasus Upah Pekerja/Buruh di Provinsi Daerah I - Himawan Gerrenove Vippianto; Mustika Prabaningrum Kusumawati (Fakultas Hukum Universitas Islam Indonesia, 2024)
In the midst of polemics over the imbalance of power between workers and employers, various phenomena of machineization of groups of workers have emerged. For this reason, this research aims to find out how the implementation of Article 4 paragraph (1) of Law Decree Number 21 of 2000 concerning Trade Unions/Labor Unions by KSPSI DIY in the wage sector?; How KSPSI DIY's efforts in preventing and handling wage disputes as a form of implementation of Article 4 paragraph (1) of Law Decree Number 21 of 2000 concerning Trade Unions/Labor Unions? This research uses an empirical method, which means that the research data is collected by studying documents or other literature data and interviews with research subjects. This research concludes that the function and role of DPD KSPSI DIY towards the implementation of Article 4 paragraph (1) of Law Decree Number 21 Year 2000 concerning Trade Unions/Labor Unions on the scale of wage disputes is present through its authority as regulated in laws and regulations, bylaws, and cultural culture that exists in KSPSI DIY as a workers' organization. The establishment of a communicative forum between workers' organizations registered under KSPSI DIY is also encouraged for the sake of preventive and repressive prevention of each working area as a trade union or trade union federation.